Producción de textos narrativos en lengua materna y su relación con la identidad cultural en estudiantes de quinto de secundaria I.E. 64479 Pastor Valencia Peña Bilingüe Intercultural Cushillo Cocha, Provincia Mariscal Ramón Castilla 2023 - Pashia Moreno, Werner Gustavo (2024)
This study was conducted to analyze the connection between the creation of narrative texts in the native language and cultural identity among 5th-grade students at I.E. 64479 PASTOR VALENCIA PEÑA, located in CUSHILLO COCHA, an intercultural bilingual school in the MARISCAL RAMÓN CASTILLA Province during the year 2023. The research perspective adopted is Transactional, with a quasi-experimental design and a descriptive correlational and cross-sectional nature. The population and selected sample consisted of 30 5th-grade students from I.E. 64479 PASTOR VALENCIA PEÑA. A survey and a questionnaire were used as the technique and instrument, respectively, for data collection, both supported by expert validation. Information analysis included descriptive techniques such as frequency, average, and percentage analysis, as well as inferential analysis to assess the proposed hypotheses. The inferential statistical analysis was performed using the Chi-Square test (X2), with a significance level set at α = 0.05% and a confidence level of 95%. As a main conclusion, a significant correlation was found between the examined variables: the production of narrative texts in the native language and cultural identity among 5th-grade students at I.E. 64479 PASTOR VALENCIA PEÑA, an intercultural bilingual school in CUSHILLO COCHA, MARISCAL RAMÓN CASTILLA Province in the year 2023.